2001
DOI: 10.1021/jf010164e
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of Compositae Plants. 2. Triterpene Diols, Triols, and Their 3-O-Fatty Acid Esters from Edible Chrysanthemum Flower Extract and Their Anti-inflammatory Effects

Abstract: The n-hexane soluble and the nonsaponifiable lipid fractions of the edible flower extract of chrysanthemum (Chrysanthemum morifolium) were investigated for triterpene diol and triol constituents. These triterpenes occur as the 3-O-fatty acid esters in the n-hexane soluble fraction from which 26 new and 6 known fatty acid esters were isolated and characterized. From the nonsaponifiable lipid fraction, 24 triterpene diols and triols were isolated, of which 3 were new compounds: (24S)-25-methoxycycloartane-3beta,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
95
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 25 publications
0
95
0
3
Order By: Relevance
“…A broad absorption peak was observed at 430 nm, which is a characteristic band for the Ag, arising from the excitation of longitudinal plasmon vibrations of AgNP in the solution. 30 The absorption peak of the CM extract was observed at 373 nm, which is typical of the absorptions of flavonoids. Flavonoids, such as luteolin-7-O-β-D-glucoside and apigenin-7-O-β-D-glucoside, are the main components of CM extract.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…A broad absorption peak was observed at 430 nm, which is a characteristic band for the Ag, arising from the excitation of longitudinal plasmon vibrations of AgNP in the solution. 30 The absorption peak of the CM extract was observed at 373 nm, which is typical of the absorptions of flavonoids. Flavonoids, such as luteolin-7-O-β-D-glucoside and apigenin-7-O-β-D-glucoside, are the main components of CM extract.…”
Section: Resultsmentioning
confidence: 91%
“…Flavonoids, such as luteolin-7-O-β-D-glucoside and apigenin-7-O-β-D-glucoside, are the main components of CM extract. 30 Therefore, the flavonoids of CM extract may play the key roles, not only to reduce the AgNO 3 solution to AgNP, but also to stabilize the nanoparticles in the solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature survey more varieties of Chrysanthemums are mainly cultivated in china such as Shen-nong Sweet Chrysanthemum, Tender Huang-ju, Chamomile Flower, Hangzhou White Chrysanthemum, Florists Chrysanthemum, etc [3][4][5] . Chrysanthemum plants belong to Asteraceae family which has low molecular components include flavonoids 6 , sesquiterpenes 7 , triterpenes 8 , and unsaturated fatty acids 9 . The volatile chemical compounds of Chrysanthemum essential oil are mainly composed of monoterpenes, sesquiterpenes, aldehydes, acids, esters and alcohols [10][11][12] .…”
Section: Introduction Of Chrysanthemum Sppmentioning
confidence: 99%
“…Its flowers contain essential oil, sesquiterpenes, flavonoids, and their glycosides. 1,2) It has been reported that these flowers have various biological activities, such as anti-oxidation, 3) anti-inflammation, 4,5) oncogenic suppression, 6) anti-mutagenicity, 7) and anti-HIV. 8) We developed chrysanthemum flower oil (CFO; Kaneka Chrysflavone TM ) as an oily fraction containing polyphenols derived from chrysanthemum flowers.…”
mentioning
confidence: 99%